Clinical significance and differential diagnosis of café-au-lait spots. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Café-au-lait spots are the early diagnostic sign of type I peripheral neurofibromatosis (NF-1). They represent the only evidence of the disease during the first years of life in the absence of congenital bone alterations and when the disease has harisen from a new gene mutation leading to a negative family history. In this article, the Authors discuss the diagnostic criteria of NF-1, highlighting their excessive strictness. However, café-au-lait spots must be differentiated from some dermatoses including the hyperchromic nevus, the congenital melanocytic nevus, and other less frequent skin conditions.